Eigenvalue assignment via uncertain state feedback controllers. Issue 5 (25th April 2019) - Siahlooei, Esmaeil; Shahzadeh Fazeli, Seyed Abolfazl; Karbassi, Seyed Mehdi
Abstract: In this paper, we propose a method for eigenvalue assignment using linear control systems containing uncertain elements. Uncertain systems are systems described by state equations which depend on uncertain parameters. In this paper, uncertainty is modeled with interval numbers. The proposed method assigns prescribed eigenvalues to a state feedback control system. Also, we introduce two interval operations to be used in our method use them. Some numerical experiments are presented to illustrate the effectiveness of the proposed method.